Female CFOs and loan contracting: Financial conservatism or gender discrimination? : an empirical test based on collateral clauses - Xixiong Xu; Yaoqin Li; Mengmeng Chang (China Journal of Accounting Research, 2016)
Based on signaling and gender discrimination theory, we examine whether chief financial officer (CFO) gender matters to bank-firm relationships and the designing of collateral clauses in bank loan contracting, and explore the potential path of influence. Data taken from Chinese listed companies between 2009 and 2012 indicate that (1) female-CFO-led firms are less likely to obtain credit loans than male-CFO-led firms; (2) female-CFO-led borrowers are more likely to be required to provide collateral for loans than male-CFO-led borrowers; and (3) banks are more inclined to claim mortgaging collateral when lending to female-CFO-led firms and prefer to guarantee collateral when lending to male-CFO-led firms. Female-CFO-led borrowers seem to be granted more unfavorable loan terms than male-CFO-led borrowers, supporting the hypothesis that female CFOs experience credit discrimination. Further analysis reveals that regional financial development helps to alleviate lending discrimination against female CFOs. Furthermore, female CFOs in SOEs are less likely than their non-SOE counterparts to experience gender discrimination in the credit market.
Keywords: G21; G32; J16; 650; Female CFOs; Loan contracting; Collateral clauses; Financial conservatism; Gender discrimination